Overview of Contributions in Geographical Analysis: Waldo Tobler. Issue 4 (13th September 2020) - Murray, Alan T.; Xu, Jing; Baik, Jiwon; Burtner, Susan; Cho, Seonga; Noi, Evgeny; Pludow, B. Amelia; Zhou, Enbo
Abstract : The academic contributions of Waldo Tobler are noteworthy and significant, spanning essentially all disciplines that involve the study of geographic phenomena. While much attention has been given to his observations of the first law of geography, there is much more substance to his larger body of research. It is especially fitting that this commemorative special issue is appearing in Geographical Analysis as Tobler published extensively in the journal, beginning in the first volume in 1969 up to volume 42 in 2010, making important contributions to quantitative theoretical geography. His research helped to build and sustain the journal, laying the foundation for what is the premier quantitative geography outlet today. This article reviews his publication activity in Geographical Analysis .